Deficits in neuromuscular control of increasing force in patients with chronic lateral epicondylitis - Chen, Yueh; Hu, Chia-Ling; Hong, Chih-Kai; Hsu, Kai-Lan; Kuan, Fa-Chuan; Chen, Wei-Li; Su, Wei-Ren; Chen, Yi-Ching; Hwang, Ing-Shiou (Frontiers in Physiology, 2023)
Objective: This study investigated the neuromuscular control of increasing and releasing force in chronic lateral epicondylitis (CLE) patients .Methods: Fifteen patients with CLE (10 males, 5 females, 46.5 ± 6.3 years) and fifteen healthy participants (9 males, 6 females, 45.3 ± 2.5 years) participated. In addition to power grip and maximal voluntary contraction (MVC) of wrist extension, force fluctuation dynamics and characteristics of inter-spike intervals (ISI) of motor units (MUs) with various recruitment thresholds in the extensor carpi radialis brevis (ECRB) and extensor carpi radialis longus (ECRL) during a designated force-tracking task with a trapezoidal target (0%-75%-0% MVC) were assessed.Results: Besides a smaller MVC of wrist extension, the patients exhibited significantly greater task errors (p = .007) and force fluctuations (p = .001) during force increment than the healthy counterparts. Nevertheless, no force variables significantly differed between groups during force release (p > .05). During force increment, the amplitudes of the motor unit action potential of the ECRB and ECRL muscles of the patients were smaller than those of the heathy counterparts (p < .001).The patient group also exhibited a higher percentage of motor units (MU) with lower recruitment threshold (< 5% MVC) in the ECRL/ECRB muscles and a lower percentage of MU with higher recruitment threshold (> 40% MVC) in the ECRB muscle, compared to the healthy group. During force increment, the patient group exhibited a higher rate of decrease in inter-spike intervals (ISIs) of motor units with lower recruitment thresholds (<10% MVC) in the ECRB and ECRL muscles, compared to the control group (p < .005).The patients with CLE exhibited more pronounced impairment in increasing force than in releasing force. This impairment in increasing force is attributed to deficits in tendon structure and degenerative changes in the larger motor units of the wrist extensors. To compensate for the neuromuscular deficits, the rate of progressive increase in discharge rate of the remaining smaller motor units (MUs) is enhanced to generate force.The deficits in neuromuscular control observed in CLE with degenerative changes cannot be fully explained by the experimental pain model, which predicts pain-related inhibition on low-threshold motor units.